2019
DOI: 10.1001/jamanetworkopen.2019.1179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxygen Saturation Index Compared With Oxygenation Index in Neonates With Hypoxemic Respiratory Failure

Abstract: Key Points Question Is oxygen saturation index (OSI) a reliable surrogate marker of oxygenation index (OI) in neonates with hypoxemic respiratory failure? Findings In this cohort study including 1442 paired OI and OSI measurements from 220 neonates, OSI was noted to correlate strongly with OI. Derived OI from OSI was in good agreement and strongly predictive of clinically relevant OI cutoffs from 5 to 25. Meaning Derived OI from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 21 publications
7
88
1
2
Order By: Relevance
“…OSI (ie, mean airway pressure  F IO 2  100/S pO 2 ) has a strong linear correlation with the oxygen index and had been validated as a noninvasive method for assessing the severity of respiratory illness in infants and children. [26][27][28] Recently, Muniraman et al 29 demonstrated that the oxygen index derived from OSI was strongly correlated (r ¼ 0.89) and may provide reliable assessment of respiratory failure on a 12 Collectively, these findings suggest that OSI is a useful metric for guiding interventions, evaluating treatment response, and identifying risk stratification in premature infants, and our results support these findings. Our data suggest that ductal patency confers a survival benefit because subjects who did not have a patent ductus arteriosus demonstrated a nearly 8-fold increase in mortality.…”
Section: Discussionsupporting
confidence: 82%
“…OSI (ie, mean airway pressure  F IO 2  100/S pO 2 ) has a strong linear correlation with the oxygen index and had been validated as a noninvasive method for assessing the severity of respiratory illness in infants and children. [26][27][28] Recently, Muniraman et al 29 demonstrated that the oxygen index derived from OSI was strongly correlated (r ¼ 0.89) and may provide reliable assessment of respiratory failure on a 12 Collectively, these findings suggest that OSI is a useful metric for guiding interventions, evaluating treatment response, and identifying risk stratification in premature infants, and our results support these findings. Our data suggest that ductal patency confers a survival benefit because subjects who did not have a patent ductus arteriosus demonstrated a nearly 8-fold increase in mortality.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to the oxygen saturation index (OSI; [FiO 2 × mean airway pressure]/SpO 2 ), the SpO 2 /FiO 2 ratio does not include the mean airway pressure. The OSI has been validated only in invasively ventilated patients in the first days of life [19][20][21] and none of the patients in this study received MV around doxapram start or during doxapram therapy. Integration of noninvasive pressure support could further improve therapy, although it is known to be an unreliable measure for the mean airway pressure in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory severity score (RSS = mean airway pressure (cmH 2 O) x FiO 2 ) and oxygen saturation index (OSI = MAP x FiO 2 × 100 ÷ SpO 2 ) were used to compare the pre-extubation respiratory conditions between the two groups [24, 25]. The RSS has been used to predict extubation readiness or the length of mechanical ventilation in preterm infants, and the OSI has been suggested to be a useful measurement to reliably assess the severity of respiratory conditions in preterm infants when the oxygen index is not available [26, 27].…”
Section: Methodsmentioning
confidence: 99%